2014
DOI: 10.1093/geront/gnu059
|View full text |Cite
|
Sign up to set email alerts
|

How Could Lay Perspectives on Successful Aging Complement Scientific Theory? Findings From a U.S. and a German Life-Span Sample

Abstract: Young, middle-aged, and older lay persons from the United States and Germany have quite similar concepts of successful aging, which they view in far more multidimensional terms than do established scientific theories (Rowe & Kahn, 1998). Given evidence that factors mentioned by laypeople do promote successful aging, considering them in more comprehensive theoretical models may enhance our understanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(113 citation statements)
references
References 47 publications
11
91
0
4
Order By: Relevance
“…The main themes derived from the responses of the elderly are essentially related to well-being orientation 10 In the presence of resources -especially those of a financial nature 11 In the engagement to life -as a concern with health care or active lifestyle 12 In having positive social relations 13 In having health and physical and mental independence 14 and in subjective and psychological well-being. 15 It is noteworthy that the denial of successful old age, even if in a few cases is usually represented in the answers of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…The main themes derived from the responses of the elderly are essentially related to well-being orientation 10 In the presence of resources -especially those of a financial nature 11 In the engagement to life -as a concern with health care or active lifestyle 12 In having positive social relations 13 In having health and physical and mental independence 14 and in subjective and psychological well-being. 15 It is noteworthy that the denial of successful old age, even if in a few cases is usually represented in the answers of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, consistent with prior studies, our results suggest that wellness resources, positive spirit and valued relationship contribute to SA [24,46,47] . For example, several studies have indicated the importance of positive spirit as essential ingredients of SA [9,23,46,48] . Our findings are also consistent with prior formulations that suggest psychological resources and behavioral adaptations, such as proactive strategies, are important aspects of SA [19,23] .…”
Section: Factors Contributing To Sa From Laypersons' Perspectivesmentioning
confidence: 99%
“…A partir de una perspectiva psicosocial, la construcción teórico-conceptual del proceso de envejecimiento exitoso ha liderado desde hace aproximadamente 30 años el conocimiento científico psicogerontológico, con efectos en la investigación básica y aplicada a nivel mundial (Bowling & Dieppe, 2005;Bowling & Ilieffe, 2006Bülow & Söderqvist, 2014;Cho, Martin, & Poon, 2015;Freund, Nikitin, & Ritter, 2009;Johnson, Sarkisian, & Williamson, 2015;Jopp et al, 2015;Kahana, Kahana, & Lee, 2014;Ouwehand, de Ridder, & Bensing, 2007;Steverink, Lindenberg, & Ormel, 1998). El envejecimiento con éxito se ha estudiado como un concepto multidimensional que abarca, trasciende y supera la buena salud (Organización Mundial de la Salud [OMS], 2002), y que está compuesto por un amplio conjunto de factores biopsicosociales, reconociendo que existe gran variabilidad interindividual en las formas de envejecer (Bowling & Ilieffe, 2011).…”
Section: Introductionunclassified
“…Se priorizó, como en investigaciones previas, el análisis en la indagación de las variables socioemocionales (Eizenman, Nesselroade, Featherman, & Rowe, 1997;Fernández-Ballesteros, Diez-Nicolás, Caprara, Barbaranelli, & Bandura, 2002;Freund & Baltes, 1998;Jopp & Smith, 2006;Lang & Carstensen, 1994;Mendes de León, 2005;Seeman, McAvay, Merrill, Albert, & Rodin, 1996) y cognitivas que predicen este fenómeno durante la vejez (Dockree, Brennan, O'Sullivan, Robertson, & O'Connell, 2015;Hogan, Mata, & Carstensen, 2013;Krueger, Wilson, Kamenetsky, Barnes, Bienias, & Bennett, 2009;Vásquez, Rodríguez, Villarreal, & Campos, 2014). Además, se buscó describir las particularidades que caracterizan a aquellas personas adultas mayores que mantienen un alto nivel de participación social y física dentro y fuera de sus hogares (Glei, Landau, Goldman, Chuang, Rodriguez, & Weinstein, 2005;Hogan et al, 2013;Johnson et al, 2015;Potočnik & Sonnentag, 2013), que ha sido definida en la publicación antecedente como criterio de clasificación del envejecimiento con éxito en distintos contextos y metodologías de análisis (Cho et al, 2015;Fernández-Ballesteros, Zamarrón, López, Molina, Díez, Montero, & Schettini, 2010;Gureje, Oladeji, Abiona, & Chatterji, 2014;Parslow, Lewis, & Nay, 2011;Jopp, Wozniak, Damarin, De Feo, Jung, & Jeswani, 2015;Kahana et al, 2014;Kahana, Kelley-Moore, & Kahana, 2012). Se consideraron también variables asociadas a condiciones de salud (Haveman-Nies, de Groot, & van Staveren, 2003;Tyrovolas, Haro, Mariolis, Piscopo, Valacchi, Tsakountakis, & Metallinos, 2014) y características sociodemográficas (Gestorf et al, 2008) presentes en el ...…”
Section: Introductionunclassified